Discovery and classification of compact radio sources in the MeerKAT Galactic Centre data - Rammala, Isabella Dineo (Rhodes University, Faculty of Science, Department of Physics and Electronics)
Access restricted. Expected release date in 2025.
Keywords: Uncatalogued